2020
DOI: 10.25259/sni_575_2020
|View full text |Cite
|
Sign up to set email alerts
|

Delayed recovery from paraplegia following resections of thoracic meningiomas

Abstract: Background: In this retrospective study, we evaluated the patterns of postoperative recovery for patients who were initially paraplegic before the excision of thoracic spine meningiomas. We also determined how the various prognostic factors impacted outcomes. Methods: Twenty patients with paraplegia underwent surgical excision of thoracic spine meningiomas at 2016– 2019. Patients’ demographics, clinical, radiological data, operative details, histopathology, and postoperative complications were recorded; pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Unlike the findings of the present study, the delay from symptom onset (also including other symptoms than loss of walking ability) to surgery was not associated with the functional outcome. Ashry et al [ 12 ] retrospectively studied the results of surgery on thoracic meningiomas in a sample of 20 paraplegic patients (75% women; median age, 49 years). Opposing the findings of this study, during the postoperative follow-up, 70% of the paraplegic patients recovered to at least assisted walking of whom all had their surgery within 2 weeks after the onset of paraplegia.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the findings of the present study, the delay from symptom onset (also including other symptoms than loss of walking ability) to surgery was not associated with the functional outcome. Ashry et al [ 12 ] retrospectively studied the results of surgery on thoracic meningiomas in a sample of 20 paraplegic patients (75% women; median age, 49 years). Opposing the findings of this study, during the postoperative follow-up, 70% of the paraplegic patients recovered to at least assisted walking of whom all had their surgery within 2 weeks after the onset of paraplegia.…”
Section: Discussionmentioning
confidence: 99%
“…also reported the surgical outcomes of 20 patients who were paraplegic due to thoracic meningiomas of whom 14 patients recovered, and all of them had surgery within 14 days from the onset of paralysis. [ 1 ] When Schwake et al . studied 88 patients with spinal meningiomas, 73% of which were thoracic, motor deficits improved with surgery in 37 of 84 patients, while two deteriorated in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Ashry et al also reported the surgical outcomes of 20 patients who were paraplegic due to thoracic meningiomas of whom 14 patients recovered, and all of them had surgery within 14 days from the onset of paralysis. [1] When Schwake et al studied 88 patients with spinal meningiomas, 73% of which were thoracic, motor deficits improved with surgery in 37 of 84 patients, while two deteriorated in the postoperative period. [5] CONCLUSION Two out of three octogenarians with long-standing, severe preoperative paraparesis/paraplegia due to thoracic meningioma significantly benefitted from 60-289 day delayed surgery.…”
Section: Functional Recovery Following Delayed Resection Of Thoracic Meningiomasmentioning
confidence: 99%